The Role of STEAM (Science, Technology, Engineering, Arts, and Mathematics) Education in Preparing a Creative and Adaptive Generation - Fien Pongpalilu; Julanos Julanos (PT. Anagata Sembagi Education, 2025)
This study explores the role of STEAM education in preparing a creative and adaptive generation in the 21st century. Using a descriptive qualitative approach supported by literature analysis, the study examines how transdisciplinary learning that integrates science, technology, engineering, arts, and mathematics cultivates creativity, cognitive flexibility, and resilience in responding to change. The findings indicate that STEAM is effective only when learning environments encourage exploration, collaboration, reflection, and authentic creation within social contexts. Without such pedagogical design, STEAM risks becoming an aesthetic project without fostering long-term competencies. The study recommends systemic transformation including teacher capacity development, redesigned assessment systems, and cross-sector collaborations to ensure that STEAM functions as an educational framework capable of shaping a creative and adaptive future generation